All-trans-retinoic acid (ATRA) plus oxaliplatin plus 5-fluorouracil/leucovorin (FOLFOX) versus FOLFOX alone as palliative chemotherapy in patients with advanced hepatocellular carcinoma and extrahepatic metastasis: study protocol for a randomized controlled trial - Shi, Jie; Sun, Juxian; Liu, Chang; Chai, Zongtao; Wang, Nanya; Zhang, Hui; Cheng, Shuqun (Current controlled trials in cardiovascular medicine, 2019)
Background Among patients with hepatocellular carcinoma (HCC), 85% of patients have an advanced disease stage at diagnosis and curative therapies cannot be performed. Prognosis has been quite poor as until recently there was no proven effective chemotherapy. Our group found that all-trans-retinoic acid (ATRA) could improve the efficacy of platinum in HCC in vivo and in vitro, thus we wish to validate the efficiency of ATRA in clinical practice. Methods This is a double-blinded, 1:1 randomized, controlled, multicenter clinical trial. Three hundred and sixty-eight patients with HCC and extrahepatic metastases will receive palliative chemotherapy at the Eastern Hepatobiliary Surgery Hospital, First Hospital of Jilin University and Fujian Provincial Cancer Hospital. Subjects will be randomly assigned to one of the two arms, either ATRA + oxaliplatin + 5-fluorouracil/leucovorin (FOLFOX4) or FOLFOX4 alone. ATRA 20 mg will be given orally three times/day for 3 days prior to the initiation of FOLFOX4. ATRA will be discontinued at the end of FOLFOX4. Discussion Overall survival rate is the primary endpoint. Secondary endpoints are time to progression according to the modified response evaluation criteria in solid tumors (mRECIST) criteria, acute and chronic adverse events, and quality of life. Trial registration Chinese Clinical Trial Registry, ChiCTR-IIR-17012916 . Registered on 9 October 2017.